Financial technology readiness for Shariah-compliant banking services: Post-merger perspectives - Kurniawati, Desi Tri; Fernando, Yudi; M. Abdi Dzil, Ikhram W.; Masyhuri, . (Emerald Publishing, 2024)
Purpose; The mergers and acquisitions impact the firm’s marketing strategy to target the potential market. To compete with conventional banks, Shariah banks have accommodated financial technology (Fintech) and digitalisation to retain existing customers and attract potential customers. Furthermore, this study aims to analyse the role of organisational trust and commitment in mediating the effect of perceived organisational support and managers’ perceptions of the readiness for Shariah-compliant Fintech adoption. Design/methodology/approach: To obtain information, 115 managers from Shariah bank in Indonesia were surveyed. The data were then analysed using PLS-SEM with SmartPLS software. Findings: Perceived organisational support became crucial in improving readiness to adopt the digitalisation initiative and adhere to Shariah norms. Moreover, organisational trust and commitment fully mediated the effect of perceived organisational support and manager’s readiness to change towards Shariah digital bank. Practical implications: Adopting Fintech and its services can offer better value to customers. Digital technology has supported the merger acquisition of Shariah bank to reduce operational costs and improve productivity and service quality. The Fintech adoption in Shariah banks needs to align with a marketing strategy that can add value, offer efficient services and ensure that all transactions are safe, transparent and Riba-free (interest charged on financial transactions). Originality/value: From Shariah bank’s perspective, the role of organisational support in Fintech adoption is limited, and there is a lack of studies investigating managers’ readiness to change in post-merger and acquisitions. This study sheds new light on how Shariah banks must offer Fintech services and adopt digital technology to remain relevant and competitive. This study provides evidence of Shariah-compliant bank readiness and organisational support and commitment enablers using two mediating mechanisms. Properly adopting Fintech can provide superior service and Shariah-compliant banking services.